The Effect of Soil-Structure Interaction (SSI) on Structural Stability and Sustainability of RC Structures - Krishnan, Ragi; Sivakumar, Vidhya Lakshmi (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The issue of SSI involves how the ground or soil reacts to a building built on top of it. Both the character of the structure and the nature of the soil have an impact on the stresses that exist between them, which in turn affects how the structure and soil beneath it move. The issue is crucial, particularly in earthquake regions. The interaction between soil and structure is an extremely intriguing factor in increasing or reducing structural damage or movement. Structures sitting on deformable soil as opposed to strong soil will experience an increase in static settlement and a decrease in seismic harm.
Keywords: soil-structure interaction; structural stability; dynamic response; fragility assessment